A LCP resin composition and its preparation method and application
By adding trace amounts of all aromatic multifunctional oligomer to the LCP resin to form a microbranched or microcrosslinked structure, the warping problem of LCP resin when injection molding into precision electronic parts is solved, and the warping performance is improved. The bending modulus improves the precision of the parts.
Patent Information
- Application Number
- CN202310454272.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-04-25
AI Technical Summary
When liquid crystal polymer (LCP) is injection molded into precision electronic parts, due to its unique leather core structure, it causes unequal shrinkage in the longitudinal direction and flow direction, which has a difference in shrinkage, causing internal stress, causing plastic parts to warp and affecting electron zero. Precision of components.
By adding trace amounts of all aromatic multifunctional oligomer to the LCP resin, a microbranched or microcrosslinked structure is formed, the skin core structure of the LCP resin is improved, and the segment regularity is damaged, thereby improving warping performance and adjusting the bending mode. quantity.
The warping performance and bending modulus of the LCP resin composition are effectively improved, the grain size is reduced, the warping deformation is reduced, and the precision of electronic components is improved.
Smart Images

Figure QLYQS_4 
Figure QLYQS_5 
Figure QLYQS_6
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to an LCP resin composition and a preparation method and application thereof. Background Art
[0002] With the development of information technology, the integration of electronic components is getting higher and higher, which requires the materials of components to be smaller and thinner. Thermoplastic liquid crystal polymer (LCP) has excellent heat resistance, mechanical properties, solvent resistance and dimensional stability, and is widely used in the field of electronics and electrical. In addition, the main chain segment of liquid crystal polymer molecules is rigid, and it is very easy to orient during melt flow and has good fluidity. Therefore, liquid crystal polymer is very suitable for injection molding of small and thin parts. However, the products molded by liquid crystal polymer have the unique skin-core structure of liquid crystal polymer, which can play a fiber reinforcement effect. However, due to its unique skin-core structure, when it is injection molded into precision electronic parts, it shrinks in anisotropic manner in the longitudinal direction and flow direction, and there is a shrinkage difference. The internal stress caused can cause the plastic part to warp, seriously affecting the precision of electronic parts. This also poses a higher challenge to the warping performance of liquid crystal polymer materials.
[0003] A common method for improving the warpage performance of liquid crystal polymers is usually to add a certain amount of chopped glass fibers and mineral fillers. For example, the invention patent with publication number CN 105111772A uses a certain amount of alkali-free glass fibers, mica powder, etc. to improve the warpage performance of liquid crystal polymers.
[0004] However, none of the above methods for improving warpage performance has been improved from the perspective of the matrix resin. Summary of the invention
[0005] Based on the defects of the prior art, the purpose of the present invention is to provide an LCP resin composition and a preparation method and application thereof. The LCP resin composition is composed of an LCP resin and a trace amount of a fully aromatic multifunctional polymer to form a micro-branched or micro-cross-linked structure, improve the skin-core structure of the LCP resin, and destroy the segment regularity of the LCP resin, thereby improving the warping performance of the LCP resin composition and adjusting the bending modulus of the LCP resin composition.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] In a first aspect, the present invention provides an LCP resin composition comprising the following raw materials in parts by weight:
[0008] 100 parts of LCP resin, 0.1-1 parts of fully aromatic multifunctional oligomer, 10-60 parts of glass fiber and 20-70 parts of filler;
[0009] The LCP resin comprises repeating units represented by the following structures: -O-Ar1-O-, -OC-Ar2-CO-, -O-Ar3-CO-, -CO-Ar4-CO-;
[0010] Wherein, -Ar1-, -Ar2-, -Ar3-, -Ar4- are each independently Any of the following:
[0011] The fully aromatic multifunctional oligomer has the following structure:
[0012]
[0013] Wherein, R1, R2, and R3 are the structure represented by formula (I) or the structure represented by formula (II):
[0014]
[0015] Wherein, n is any number among 1, 2, 3, 4, 5, and 6, n in R1, R2, and R3 are the same or different positive integers, and -Ar5- is R4 and R5 are each independently a carboxyl group or an acetoxy group.
[0016] The LCP resin of the present invention comprises four repeating units: -O-Ar1-O-, -OC-Ar2-CO-, -O-Ar3-CO-, -CO-Ar4-CO-, wherein -Ar1-, -Ar2-, -Ar3-, -Ar4- are each independently Any one of the above has good processing performance, and the LCP resin having the above repeating unit structure can fully undergo ester exchange reaction with a trace amount of the fully aromatic multifunctional oligomer to form a micro-branched or micro-crosslinked structure, reduce the grain size of the LCP resin composition, and thus improve the warpage performance of the resin composition. The amount of the fully aromatic multifunctional oligomer selected by the present invention needs to be strictly controlled. If the amount of the fully aromatic multifunctional oligomer is too small, the degree of crosslinking between the fully aromatic multifunctional oligomer and the LCP resin is too low, resulting in the grain size of the LCP resin composition being too large, which is obviously not conducive to improving the warpage performance of the LCP resin composition, and is not conducive to adjusting the bending modulus of the LCP resin composition to an appropriate range; if the amount of the fully aromatic multifunctional oligomer is too much, the degree of crosslinking between the fully aromatic multifunctional oligomer and the LCP resin is too high, and it is easy to form an infusible material, which affects the application of the LCP resin composition.
[0017] As a preferred embodiment of the present invention, the LCP resin has a melting point of 302 to 372° C. and a shear viscosity of 10 to 30 Pa·s.
[0018] As a preferred embodiment of the present invention, in the repeating unit of the LCP resin, the molar content of -O-Ar1-O- is 10 to 30%, the molar content of -OC-Ar2-CO- is 8 to 20%, the molar content of -O-Ar3-CO- is 40 to 80%, and the molar content of -OC-Ar4-CO- is 2 to 10%.
[0019] Furthermore, among the components of the LCP resin, the molar content of -O-Ar1-O- is 20-25%, the molar content of -OC-Ar2-CO- is 17-18%, the molar content of -O-Ar3-CO- is 50-60%, and the molar content of -OC-Ar4-CO- is 3-7%.
[0020] Furthermore, -Ar1- is -Ar2- is -Ar3- is -Ar4- is
[0021] As a preferred embodiment of the present invention, the LCP resin is obtained by reacting HO-Ar1-OH, HOOC-Ar2-COOH, HO-Ar3-COOH, HOOC-Ar4-COOH and an acylating agent, wherein the molar ratio of HO-Ar1-OH, HOOC-Ar2-COOH, HO-Ar3-COOH and HOOC-Ar4-COOH is: HO-Ar1-OH: HOOC-Ar2-COOH: HO-Ar3-COOH: HOOC-Ar4-COOH = (10-30): (8-20): (40-80): (2-10).
[0022] Furthermore, the molar ratio of HO-Ar1-OH, HOOC-Ar2-COOH, HO-Ar3-COOH and HOOC-Ar4-COOH is: HO-Ar1-OH: HOOC-Ar2-COOH: HO-Ar3-COOH: HOOC-Ar4-COOH = (20-25): (17-18): (50-60): (3-7).
[0023] As a preferred embodiment of the present invention, R4 is a carboxyl group, and R5 is an acetoxy group.
[0024] As a preferred embodiment of the present invention, the fully aromatic multifunctional oligomer is obtained by reacting the following reactants:
[0025] (1) Trimesic acid or pyrogallol;
[0026] (2) at least one of HO-Ar5-COOH, HOOC-Ar5-COOH, and HO-Ar5-OH, wherein -Ar5- is
[0027] (3) Acylation agent.
[0028] Further, the fully aromatic multifunctional oligomer is obtained by reacting the following reactants:
[0029] (1) Trimesic acid or pyrogallol;
[0030] (2) HO-Ar5-COOH, -Ar5- is
[0031] (3) Acylation agent.
[0032] Furthermore, the molar ratio of reactant (1) to reactant (2) is 1:(3-24).
[0033] If trimesic acid, HO-Ar5-COOH and an acylating agent react, the prepared fully aromatic multifunctional oligomer has a structure shown in formula (I); if pyrogallol, HO-Ar5-COOH and an acylating agent react, the prepared fully aromatic multifunctional oligomer has a structure shown in formula (II).
[0034] The study found that the relative molar proportion of the repeating unit -O-Ar3-CO- in the repeating unit of LCP resin is controlled at 50-60%, and -Ar5- is When the resin is treated with a small amount of oligomer, the processing performance of the resin is better, and the repeating unit is close to the side chain monomer structure in the wholly aromatic multifunctional oligomer. The addition of a small amount of oligomer has little effect on other physical properties of the LCP resin composition.
[0035] As a preferred embodiment of the present invention, the molecular weight of the wholly aromatic multifunctional oligomer is 570 to 2370 g / mol.
[0036] As a preferred embodiment of the present invention, the mass ratio of the wholly aromatic multifunctional oligomer to the LCP resin is (0.2-0.8):100.
[0037] As a preferred embodiment of the present invention, the filler is an inorganic flake filler, and the inorganic flake filler is selected from at least one of talc powder and mica powder.
[0038] The mass ratio of the glass fiber, filler and LCP resin is (3-6): (3-5): 10. The present invention selects filler and glass fiber to synergistically improve the warping performance of the LCP resin composition. When the amount of glass fiber and filler meets the above conditions, the warping property of the LCP resin composition is greatly improved, making the LCP resin composition suitable for electronic components.
[0039] In a second aspect, the present invention provides a method for preparing a low-warpage LCP resin composition as described in the first aspect, comprising the following steps:
[0040] The LCP resin, the wholly aromatic multifunctional oligomer, the glass fiber and the filler are mixed and then blended and extruded through a twin-screw extruder to obtain the LCP resin composition.
[0041] As a preferred embodiment of the present invention, during the co-extrusion by the twin-screw extruder, the extrusion temperature is Tm-30°C to Tm+30°C, and the screw speed is 200 to 600 rpm, wherein Tm is the melting point of the LCP resin.
[0042] In a third aspect, the present invention provides a use of the low-warpage LCP resin composition as described in the first aspect in the preparation of electronic components.
[0043] Furthermore, the electronic components include thin-walled parts such as memory card slots and computer fans.
[0044] The beneficial effect of the present invention is that the present invention provides a low-warpage LCP resin composition and a preparation method and application thereof. The LCP resin composition is prepared by combining a specific LCP resin with a trace amount of a fully aromatic multifunctional oligomer to form micro-branching or micro-crosslinking, thereby improving the skin-core structure of the LCP resin and destroying the segment regularity of the LCP resin, thereby improving the warpage performance and bending modulus of the LCP resin composition. DETAILED DESCRIPTION
[0045] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.
[0046] The materials used in the embodiments and comparative examples are as follows:
[0047] LCP resin is prepared by the following method:
[0048] (1) Under nitrogen conditions, para-hydroxybenzoic acid (HBA), biphenol (BP), terephthalic acid (TA), isophthalic acid (IA) and acetic anhydride are added into a reactor in a certain molar ratio, and an acylation reaction is carried out under the action of acetic anhydride. The reaction temperature is 100° C. to 180° C., and the reaction time is 0.5 to 4 hours;
[0049] (2) After the acylation reaction is completed, the pressure in the reactor is maintained at normal pressure, and the temperature is increased to 200° C. to 310° C. at a rate of 0.1 to 5° C. / min, and acetic acid and unreacted acetic anhydride molecules are discharged from the rectification column. When the amount of acetic acid received reaches more than 90 wt % of the theoretical value, the pressure in the reactor is reduced to 5 to 40 kPa, and the pressure is maintained at this reduced pressure and the reaction system is heated to 330 to 400° C. When the stirring power reaches the set value, the material is discharged, cooled and granulated to obtain a prepolymer;
[0050] (3) The prepolymer is solid-phase polymerized in a solid-phase polymerization container to obtain an LCP resin.
[0051] The melting point, crystallization temperature and shear viscosity of LCP resin were tested. The test steps are as follows:
[0052] (1) Melting point and crystallization temperature: measured by using DSC 200F3 manufactured by NETZSCH Company, heating from room temperature to 390°C at a heating rate of 20°C / min, then cooling to room temperature at 20°C / min, and finally heating to 390°C at 20°C / min; the highest point of the melting peak of the second heating curve was taken as the melting point, and the lowest point of the crystallization peak of the first cooling curve was taken as the crystallization temperature;
[0053] (2) Shear viscosity: tested using a Malvern capillary rheometer at a temperature of 20°C above the melting point and a shear rate of 1000 s -1 , measured using a die with an inner diameter of 1 mm and a length of 20 mm.
[0054] The molar ratio of LCP resin 1: HBA, BP, TA, IA and acetic anhydride is HBA: BP: TA: IA: acetic anhydride = 60: 20: 17: 3: 105; the melting point of LCP resin 1 is 362°C, the shear viscosity is 15 Pa·s, and in the repeating unit of LCP resin 1, The molar content is 60%, The molar content is 20%, The molar content is 17%, The molar content is 3%.
[0055] The molar ratio of LCP resin 2: HBA, BP, TA, IA and acetic anhydride is HBA: BP: TA: IA: acetic anhydride = 50: 25: 18: 7: 105; the melting point of LCP resin 2 is 335°C, the shear viscosity is 21 Pa·s, and in the repeating unit of LCP resin 2, The molar content is 50%, The molar content is 25%, The molar content is 18%, The molar content is 7%.
[0056] The molar ratio of LCP resin 3: HBA, BP, TA, IA and acetic anhydride is HBA: BP: TA: IA: acetic anhydride = 40: 30: 20: 10: 105; the melting point of LCP resin 3 is 302°C, the shear viscosity is 30 Pa·s, and in the repeating unit of LCP resin 3, The molar content is 40%, The molar content is 30%, The molar content is 20%, The molar content is 10%.
[0057] The molar ratio of LCP resin 4: HBA, BP, TA, IA and acetic anhydride is HBA: BP: TA: IA: acetic anhydride = 80: 10: 8: 2: 105; the melting point of LCP resin 4 is 372°C, the shear viscosity is 30 Pa·s, and in the repeating unit of LCP resin 4, The molar content is 80%, The molar content is 10%, The molar content is 8%, The molar content is 2%.
[0058] The molar ratio of LCP resin 5: HBA, BP, IA and acetic anhydride is HBA: BP: IA: acetic anhydride = 60: 20: 20: 105; the melting point of LCP resin 5 is 322°C, the shear viscosity is 27 Pa·s, and in the repeating unit of LCP resin 5, The molar content is 60%, The molar content is 20%, The molar content is 20%.
[0059] The molar ratio of LCP resin 6: HBA, BP, TA and acetic anhydride is HBA: BP: TA: acetic anhydride = 60: 20: 20: 105; the melting point of LCP resin 6 is 389°C, the shear viscosity is 35 Pa·s, and in the repeating unit of LCP resin 6, The molar content is 60%, The molar content is 20%, The molar content is 20%.
[0060] The fully aromatic multifunctional oligomers were prepared by the following method:
[0061] Prepare a reaction vessel with a stirrer, monomer feed port, reflux condenser, thermometer, and nitrogen inlet, replace the gas in the reactor with nitrogen, and add the reactants respectively. Place the reactor in a 240℃ molten salt for full reflux for 2 hours, and then start to produce acetic acid. When the acetic acid production reaches a certain value, stop the reaction, pour out the reactants, cool them, crush them and grind them into powder to obtain a fully aromatic multifunctional oligomer. The infrared spectrum of the product shows that at 1735cm-1 There is a stretching vibration peak of lipid C=O at .
[0062] The molecular weight of the fully aromatic multifunctional oligomer 1 is 930 g / mol, and the structural formula is as follows:
[0063]
[0064] The reactants are trimesic acid, p-hydroxybenzoic acid and acetic anhydride, and the molar ratio of the reactants is trimesic acid: p-hydroxybenzoic acid: acetic anhydride = 1:6:6.3.
[0065] The molecular weight of the fully aromatic multifunctional oligomer 2 is 1692 g / mol, and the structural formula is as follows:
[0066]
[0067] The reactants are pyrogallol, p-hydroxybenzoic acid and acetic anhydride, and the molar ratio of the reactants is pyrogallol: p-hydroxybenzoic acid: acetic anhydride = 1:12:12.6.
[0068] The reactants are pyrogallol, p-hydroxybenzoic acid, m-hydroxybenzoic acid and acetic anhydride, and the molar ratio of the reactants is pyrogallol: p-hydroxybenzoic acid, m-hydroxybenzoic acid: acetic anhydride = 1:2:1:6.3.
[0069] The molecular weight of the fully aromatic multifunctional oligomer 3 is 612 g / mol, and the structural formula is as follows:
[0070]
[0071] The reactants are trimesic acid, hydroquinone, and acetic anhydride, and the molar ratio of the reactants is trimesic acid: hydroquinone: acetic anhydride = 1:3:3.15.
[0072] The molecular weight of the fully aromatic multifunctional oligomer 4 is 570 g / mol, and the structural formula is as follows:
[0073]
[0074] The reactants are pyrogallol, terephthalic acid and acetic anhydride, and the molar ratio of the reactants is pyrogallol: terephthalic acid: acetic anhydride = 1:3:1.05.
[0075] The molecular weight of the fully aromatic multifunctional oligomer 5 is 2370 g / mol, and the structural formula is as follows:
[0076]
[0077] The reactants are: trimesic acid, p-hydroxybenzoic acid, and acetic anhydride; the molar ratio of the reactants is 1:18:18.9.
[0078] The molecular weight of the fully aromatic multifunctional oligomer 6 is 3090 g / mol, and the structural formula is as follows:
[0079]
[0080] The reactants are trimesic acid, p-hydroxybenzoic acid and acetic anhydride, and the molar ratio of the reactants is trimesic acid: p-hydroxybenzoic acid: acetic anhydride = 1:24:25.2.
[0081] The molecular weight of the fully aromatic multifunctional oligomer 7 is 612 g / mol, and the structural formula is as follows:
[0082]
[0083] The reactants are trimesic acid, resorcinol and acetic anhydride, and the molar ratio of the reactants is trimesic acid: resorcinol: acetic anhydride = 1:3:3.15.
[0084] Glass fiber: Model is 584, manufactured by China Jushi Co., Ltd.
[0085] Talc: GH 903A, manufactured by Guilin Talc Technology Development Co., Ltd.
[0086] Unless otherwise specified, the materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the raw materials used in each parallel experiment are of the same kind.
[0087] Examples 1 to 17 and Comparative Examples 1 to 8
[0088] Examples 1 to 17 and Comparative Examples 1 to 8 respectively provide an LCP resin composition and a preparation method thereof. The components of the LCP resin composition are shown in Tables 1 to 3.
[0089] The preparation method of the LCP resin composition comprises the following steps:
[0090] After the raw materials are uniformly mixed, they are blended and extruded through a twin-screw extruder to obtain a low-warpage LCP resin composition;
[0091] During the blending and extrusion by the twin-screw extruder, the extrusion temperature is: Tm-30°C in the first zone, Tm-10°C in the second zone, Tm+30°C in the third zone, Tm-20°C in the fourth zone, Tm-20°C in the fifth zone, Tm-20°C in the sixth zone, Tm-20°C in the seventh zone, Tm+10°C in the eighth zone, and Tm+30°C in the ninth zone; the screw speed is 400 rpm, wherein Tm is the melting point of the corresponding LCP resin.
[0092] Table 1
[0093]
[0094] Table 2
[0095] Weight Example 13 Embodiment 14 Embodiment 15 Example 16 Embodiment 17 LCP resin 1 100 100 100 100 LCP Resin 4 100 Fully aromatic multifunctional oligomer 1 0.5 Fully aromatic multifunctional oligomer 2 Fully aromatic multifunctional oligomer 3 0.5 Fully aromatic multifunctional oligomer 4 0.5 Fully aromatic multifunctional oligomer 5 0.5 Fully aromatic multifunctional oligomer 7 0.5 Fiberglass 40 40 40 40 40 talcum powder 50 50 50 50 50
[0096] Table 3
[0097]
[0098] In order to verify the performance of the LCP resin composition of the present invention, the products prepared in each embodiment and comparative example were subjected to the following performance tests, and the specific steps are as follows:
[0099] (1) Warping deformation: For a sample with a length of 100 mm and a thickness of 1.5 mm, place the square plate on a marble flat plate, fix its center close to the marble plane, and measure the height difference between the edge of the sample and the center of the sample with a vernier caliper;
[0100] (2) Flexural modulus: The sample with injection molding length of 100 mm and thickness of 1.5 mm was tested in accordance with GB / T9341-2008 Determination of bending properties of plastics. The test conditions were: span 64 mm, deflection 10 mm.
[0101] (3) XRD half-peak width: The size of XRD half-peak width reflects the change of grain size. Grain size will affect the warpage performance of resin. If the grain size is too large or too small, the resin composition will be too rigid or too soft, which will increase the warpage. The X-ray diffraction method is used for measurement, and two-dimensional wide-angle XRD test is used; the sample is placed on the stage perpendicular to the incident light, and the experiment is carried out on a Xeuss2.0 device (Xenocs, France) equipped with a Cu Kα X-ray light source (λ=0.154nm). The Pilatus3R 200K-A detector (pixel 490×400 pixels) is used to collect 2D spectra, and the spectrum is integrated along 0-360° using Foxtrot software to obtain a 1D XRD curve; the half-peak width is calculated by the software; the distance from the sample to the detector in the experiment is 170nm.
[0102] (4) Infusibles: Inject 100 plates with a length and width of 10 cm and a thickness of 0.8 mm. Visually observe whether there are protrusions or white spots on the surface. Record the total number of protrusions and white spots in every 100 plates, i.e., the number of infusibles.
[0103] The test results are shown in Tables 4 to 6.
[0104] Table 4
[0105]
[0106] Table 5
[0107] Test items Example 13 Embodiment 14 Embodiment 15 Example 16 Embodiment 17 Flexural modulus / MPa 8310 8010 8340 7240 9210 XRD half peak width 4.18 4.24 4.17 4.38 4.08 Warpage / mm 0.11 0.12 0.12 0.18 0.15 Infusible none none none none none
[0108] Table 6
[0109] Test items Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Flexural modulus / MPa 10300 6580 6320 9870 10800 10200 6370 12800 XRD half peak width 4.01 4.43 4.51 4.04 4.02 4.01 4.45 3.87 Warpage / mm 0.42 0.29 0.35 0.38 0.43 0.39 0.37 0.56 The amount of unmelted material none none 9 none 39 none none none
[0110] By comparing the test results of Examples 1 to 4 and Comparative Examples 2 and 5, it can be seen that too little filler is added in Comparative Example 2, the measured XRD half-peak width is larger, and the warpage deformation is significantly larger. This is because the addition amount of glass fiber and talcum powder is too little. Although the glass fiber and talcum powder can be evenly dispersed in the resin composition, the crystallinity of the resin composition is small, but the warpage performance of the resin composition cannot be effectively improved; the XRD half-peak width measured in Comparative Example 5 is small, which indicates that too much filler is added, agglomeration occurs in the resin composition, the crystallinity of the resin composition is too large, and even infusible materials are produced, which is obviously not conducive to improving the warpage performance of the resin composition, nor is it conducive to controlling the flexural modulus of the resin composition within an appropriate range; in Examples 1 to 4, Examples 1 to 2 and 4 are blended with LCP resin by appropriate amounts of glass fiber and talcum powder, so that the LCP resin composition maintains an appropriate flexural modulus, and the warpage performance is effectively improved, and the warpage deformation is ≤0.10.
[0111] By comparing the test results of Examples 1, 5-6, 10-11, Comparative Examples 1 and Comparative Examples 3-4, it can be seen that with the increase of the wholly aromatic multifunctional polymers, the XRD half-peak width shows a downward trend. This is because the increase in the polymers forms a micro-branched and cross-linked structure, which breaks up the regularity of the molecular chain segments. Compared with Examples 1, 5-6 and 10-11, no fully aromatic multifunctional polymer was added to the resin composition of Comparative Example 1, and too little fully aromatic multifunctional polymer was added to Comparative Example 4. The XRD half-peak widths measured for both were significantly smaller, and the warpage deformations were significantly larger, which indicates that the resin crosslinking degree is too low, resulting in a large crystallinity of the resin composition, which is obviously not conducive to improving the warpage performance of the resin composition, and is also not conducive to controlling the bending modulus of the resin composition within an appropriate range; the XRD half-peak width measured in Comparative Example 3 is significantly larger, resulting in a significantly larger warpage deformation of the LCP resin composition, and infusible materials are produced; this may be due to the excessive addition of fully aromatic multifunctional polymers in Comparative Example 3, the high resin crosslinking degree, the large crystallinity of the resin composition, and the production of infusible materials, which is obviously not conducive to improving the warpage performance of the resin composition.
[0112] By comparing the test results of Examples 5, 7, 13 to 16 and Comparative Example 6, it can be seen that the XRD half-peak width of Comparative Example 6 is too small, while the bending modulus and warpage deformation are too large, which indicates that the molecular weight of the fully aromatic multifunctional polymer added in Comparative Example 6 is too large, cross-linked with the LCP resin, and the degree of branching and cross-linking is low, which has little effect on the crystallinity of the resin composition; the difference between Example 13 and Example 16 is that the side chains of the polymer in Example 13 contain para-phenyl groups, and the side chains of the polymer used in Example 16 contain meta-phenyl groups, and the warpage deformation of Example 13 is smaller.
[0113] Compared with Example 5, the LCP resins of Comparative Examples 7 to 9 have only three repeating unit structures, and the warpage performance of the resin compositions is significantly worse.
[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A LCP resin composition, characterized in that The composition comprises the following components in parts by weight: 100 parts of LCP resin, 0.1-1 parts of fully aromatic multifunctional oligomer, 10-60 parts of glass fiber and 20-70 parts of filler; The LCP resin comprises repeating units of the following structure: -O-Ar1-O-, -OC-Ar2-CO-, -O-Ar3-CO-, -OC-Ar4-CO-; Among them, -Ar1- is , -Ar2- is , -Ar3- is , -Ar4- is ; The fully aromatic multifunctional oligomer has the following structure: ; Wherein, R1, R2, and R3 are the structures shown in formula (I) or (II): (I), (Ⅱ); Wherein, n is any number among 1, 2, 3, 4, 5, and 6, n in R1, R2, and R3 are the same or different positive integers, and -Ar5- is or , R4 and R5 are each independently carboxyl or acetoxy; The filler is an inorganic flake filler.
2. The LCP resin composition according to claim 1, characterized in that The LCP resin has a melting point of 302-372° C. and a shear viscosity of 10-30 Pa·s.
3. The LCP resin composition according to claim 1, wherein In the repeating units of the LCP resin, the molar content of -O-Ar1-O- is 10-30%, the molar content of -OC-Ar2-CO- is 8-20%, the molar content of -O-Ar3-CO- is 40-80%, and the molar content of -OC-Ar4-CO- is 2-10%.
4. The LCP resin composition according to claim 1, wherein The mass ratio of the wholly aromatic multifunctional oligomer to the LCP resin is (0.2-0.8):
100.
5. The LCP resin composition according to claim 1, characterized in that The mass ratio of the glass fiber, filler and LCP resin is (3-6): (3-5):
10.
6. The LCP resin composition according to claim 1, characterized in that The inorganic flake filler is selected from at least one of talc powder and mica powder.
7. A method for preparing a LCP resin composition as claimed in any one of claims 1 to 6, characterized in that: The steps include: The LCP resin, the wholly aromatic multifunctional oligomer, the glass fiber and the filler are mixed and then blended and extruded through a twin-screw extruder to obtain a low-warpage LCP resin composition.
8. The method for preparing the LCP resin composition according to claim 7, wherein: During the co-extrusion by the twin-screw extruder, the extrusion temperature is Tm-30°C to Tm+30°C, and the screw speed is 200 to 600 rpm, wherein Tm is the melting point of the LCP resin.
9. Use of the LCP resin composition according to any one of claims 1 to 6 in the preparation of electronic components.
Citation Information
Patent Citations
Dendritic polyester, method for producing the same, and thermoplastic resin composition
CN101415748A
Low-warpage liquid crystal polymer (LCP) and preparation method thereof
CN105111772A
Cited By
High-performance LCP (Liquid Crystal Polymer) resin and preparation method thereof
CN122011713A